2011
DOI: 10.1177/0363546511428866
|View full text |Cite
|
Sign up to set email alerts
|

Does Double-Row Rotator Cuff Repair Improve Functional Outcome of Patients Compared With Single-Row Technique?

Abstract: Through a comprehensive literature search and meta-analysis of current arthroscopic rotator cuff repairs, we found that the single-row repairs did not differ from the double-row repairs in functional outcome scores. The double-row repairs revealed a trend toward a lower radiographic proven retear rate, although the data did not reach statistical significance. There may be a concerning trend toward higher retear rates in patients undergoing a single-row repair, but further studies are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
83
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 44 publications
(82 reference statements)
1
83
0
4
Order By: Relevance
“…Saridakis and Jones 4 came to a similar conclusion that there appears to be a benefit of structural healing with DR when compared with SR. However, in another systematic review, DeHaan et al 3 could not make the same conclusion, stating that there was a trend toward a lower radiographic retear rate for DR when compared with SR but the difference was not statistically significant.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Saridakis and Jones 4 came to a similar conclusion that there appears to be a benefit of structural healing with DR when compared with SR. However, in another systematic review, DeHaan et al 3 could not make the same conclusion, stating that there was a trend toward a lower radiographic retear rate for DR when compared with SR but the difference was not statistically significant.…”
mentioning
confidence: 91%
“…The incidence of retear after arthroscopic rotator cuff repair varies widely in the literature, with reported rates of up to 94% in patients with large and massive tears. 1 Although the clinical impact of rotator cuff retears remains a point of controversy in the literature, [2][3][4][5] several studies have shown that retears affect functional recovery. [6][7][8][9] Several patient-related risk factors associated with retear have been identified.…”
mentioning
confidence: 99%
“…Retear rates of 10% to 30% have been found in doublerow techniques with higher rates (40% to 64%) in those patients with large-to-massive tears. 3,4,6,[8][9][10][11] The triple-row modification of the suture bridge construct, using a third row of fixation placed between the typical medial and lateral rows, was developed to help improve the rotator cuff footprint contact area and pressure by anatomic positioning of the cuff before tying the medial anchors. Medial-row anchors are placed in a standard fashion and the sutures are passed through the cuff medially but are not tied.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Furthermore, retear rates of 10% to 30% have been found in double-row techniques with higher rates (40% to 64%) in those patients with largeto-massive tears ( 3 cm). 3,4,6,[8][9][10][11] When using this technique for larger tears, it can be difficult to get the lateral portion of the rotator cuff into an anatomic position. There is concern that this results in limited rotator cuff footprint contact area.…”
mentioning
confidence: 99%
“…79 The detail of the repair is important: it is generally currently accepted that a double-row fixation technique onto a prepared bone surface (or 'footprint') provides the most durable method of re-implantation of a RCT. [80][81][82][83][84][85] The bone must be biologically competent (i.e. it must be able to generate growth factors in a milieu of mesenchymal stem cells) and be sufficiently mechanically stable to hold the fixation devices.…”
Section: Treatment Specified By Patho-biomechanicsmentioning
confidence: 99%